Evaluation of applicants unable to perform military service due to eye disease in terms of disease etiology and preventability: A cross-sectional study - Berire Şeyma Durmuş Ece; İrem Güneş (Ovid Technologies (Wolters Kluwer Health), 2023)
Purpose: Our study’s goal was to investigate the individuals who took a pre-military examination and were pronounced “unfit for military service,” in terms of etiological grouping, legal blindness, and whether or not the illness could have been prevented. Methods: The files of 174 individuals deemed “unfit for military service” due to eye disease at the State Hospital Ophthalmology Department between January 2018 and January 2022 were retrospectively evaluated. The disorders were classified as refractive error, strabismus, amblyopia-related, congenital, hereditary, infectious/inflammatory, degenerative, and trauma-related pathologies. The reasons for unsuitability for military service were classified according to monocular and binocular legal blindness, preventability, and treatability with early diagnosis. Results: In our study, the reasons associated with refractive error, strabismus, and amblyopia were placed first in the etiology of unsuitability for military service (40.2%). The next most prevalent condition was trauma (19.5%), which was followed by degenerative (18.4%), congenital (10.9%), hereditary (6.9%), and infectious/inflammatory disorders (4.0%). There was a history of penetrating trauma in 79.4% of trauma patients and blunt trauma in 20.6% of patients. When the etiology was evaluated, 19.5% were in preventable and 51.2% were in treatable group with early diagnosis. In our study, legal blindness was detected in 116 patients. Of these patients, 79% had monocular legal blindness and 21% had binocular legal blindness. Conclusion: It is vital to investigate the etiology of visual disorders, control preventable causes, and determine the methods that will provide early diagnosis and treatment of curable causes.
Keywords: Vision Disorders; vision disorders; RE1-994; Amblyopia; Blindness; Refractive Errors; Strabismus; Ophthalmology; Cross-Sectional Studies; Military Personnel; military personnel; Humans; Original Article; military medicine; blindness; Retrospective Studies; 3. Good health